Ectomycorrhizal fungi increase the vitality of Norway spruce seedlings under the pressure of Heterobasidion root rot in vitro but may increase susceptibility to foliar necrotrophs - Velmala, Sannakajsa; Vuorinen, I.; Uimari, Anne; Piri, Tuula; Pennanen, Taina (Elsevier, 2018)
We tested if root colonization by ectomycorrhizal fungi (EMF) could alter the susceptibility of Norway spruce (Picea abies) seedlings to root rot infection or necrotic foliar pathogens. Firstly, spruce seedlings were inoculated by various EMF and challenged with Heterobasidion isolates in triaxenix synthesis tubes. The ascomycete EMF Meliniomyces bicolor, that had showed strong antagonistic properties towards root rot causing Heterobasidion in vitro, protected spruce seedlings effectively against root rot. Secondly, spruce seedlings, inoculated with M. bicolor or the forest humus layer, were subjected to necrotrophic foliar pathogens (Botrytis cinerea or Gremmeniella abietina) in conventional forest nursery conditions on variable peat substrates. Botrytis cinerea infection after winter was mild and the level of needle damage was independent of growth substrate and EMF colonization. Needle damage severity caused by G. abietina was high in seedlings grown in substrates with high nutrient availability as well as in seedlings with well-established EMF communities in their roots. These results show that albeit M. bicolor is able to protect spruce seedlings against Heterobasidion root rot in axenic cultures it fails to induce systemic protection against foliar pathogens. We also point out that unsterile inoculum sources, such as the forest humus layer, should not be considered for use in greenhouse conditions as they might predispose seedlings to unintended needle damages.
Keywords: Botrytis cinerea; forest nurseries; Gremmeniella abietina; Meliniomyces bicolor; Picea abies; taimitarhat; integroitu torjunta; integrated pest management